Bones of contention : contestations over human remains in the Eastern Cape - Mkhize, Nomalanga (Rhodes University, Faculty of Humanities, Department of History, 2007)
This thesis examines three contestations involving human remains which have arisen in the Eastern Cape over the past fifteen years. It shows that the value or meaning attached to human remains is constructed through the socio-historical dynamics out of which these contestations arise. The meaning and value of human remains is neither inherent nor neutral. In Ndancama's case, the need for housing in Fingo Village led hundreds of poor residents to settle on the township's Old Cemetery in 1972. Basic material needs trumped concerns for those buried in the cemetery. When the post-apartheid municipality sought to provide sewerage and housing infrastructure for Ndancama in 2003, its development plans were constrained by new heritage legislation which protects historic cemeteries. Residents insisted that their infrastructural needs were of primary importance. In 1993, the unearthing of human remains at the Old Military Cemetery in King William's Town created a thirteen year long saga which was only resolved with the reburial of the remains in 2006. The presence of the remains proved problematic for a number of reasons. Local authorities failed to rebury the remains speedily. The burden to store them fell on the Kaffrarian Museum which came under fire because this was considered unethical in the postapartheid era. The identity of the remains became a bone of contention in 2006 when the new Amathole District Municipality concluded that the remains were those of victims who died in the 1856-57 Great Cattle Killing. The remains and their reburial became symbols of past injustice and present restoration of African heritage. The 1996 quest by 'Nicholas Gcaleka', a 'self-styled' chief and traditional healer, to search for King Hintsa's skull in the United Kingdom provoked unprecedented public engagement with the incomplete narrative on the fate of Hintsa's body. The power to represent history, and the methods through which historical truth is discovered were at the heart of the contestation. Elites such as the Xhosa Royal and the white scientific establishment were considered neither credible nor authoritative on this historical matter. Public support for Gcaleka revealed that many South Africans sought just recompense for colonial injustices.
Keywords: Dead -- Political aspects -- South Africa; Human body -- Symbolic aspects; Human remains (Archaeology) -- Repatriation; Human remains (Archaeology) -- Repatriation -- South Africa -- Eastern Cape; Xhosa (African people) -- Social life and customs; Eastern Cape (South Africa) -- Social life and customs; Eastern Cape (South Africa) -- History